Eosinophil: A Nonnegligible Predictor in COVID-19 Re-Positive Patients - Li, Xiaolu; Yin, Deqing; Yang, Yanyan; Bi, Chunhua; Wang, Zhibin; Ma, Guangren; Fu, Xiuxiu; Ji, Shengxiang; Jiang, Fachun; Yu, Tao (Frontiers in Immunology, 2021)
Although vaccine resources are being distributed worldwide, insufficient vaccine production remains a major obstacle to herd immunity. In such an environment, the cases of re-positive occurred frequently, and there is a big controversy regarding the cause of re-positive episodes and the infectivity of re-positive cases. In this case-control study, we tracked 39 patients diagnosed with COVID-19 from the Jiaodong Peninsula area of China, of which 7 patients tested re-positive. We compared the sex distribution, age, comorbidities, and clinical laboratory results between normal patients and re-positive patients, and analyzed the correlation between the significantly different indicators and the re-positive. Re-positive patients displayed a lower level of serum creatinine (63.38 ± 4.94 U/L vs. 86.82 ± 16.98 U/L; P =0.014) and lower albumin (34.70 ± 5.46 g/L vs. 41.24 ± 5.44 g/L, P =0.039) at the time of initial diagnosis. In addition, two positive phases and the middle negative phase in re-positive patients with significantly different eosinophil counts (0.005 ± 0.005 × 109/L ; 0.103 ± 0.033 × 109/L; 0.007 ± 0.115 × 109/L; Normal range: 0.02-0.52 × 109/L). The level of eosinophils in peripheral blood can be used as a marker to predict re-positive in patients who once had COVID-19.